2011
DOI: 10.1007/s10765-011-1094-8
|View full text |Cite
|
Sign up to set email alerts
|

Normal Spectral Emissivity of Steel HS2-9-1-8 at 684.5 nm

Abstract: Within this study, the normal spectral emissivity at melting and in the liquid state of the highly alloyed steel HS2-9-1-8 at 684.5 nm is presented. Measurements were performed with a division-of-amplitude photopolarimeter, as part of a fast ohmic pulse heating system reaching heating rates of about 10 8 K · s −1 . The determined data show an increasing emissivity throughout the liquid phase, with the value at liquidus T liquidus = 1687 K being ε = 0.371 and at the highest temperature T max = 2307 K of ε = 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…8), 10) and 11). As pointed out above, obvious oscillations of normal spectral emissivity appears only at the first several min from the heating start in this work, whereas those reported in the literature 2,[8][9][10][11]14) appeared at very different heating times, typically from several seconds to an hour in the oxidizing surroundings.…”
Section: Strong Oscillation Of the Normal Spectral Emissivitysupporting
confidence: 49%
See 4 more Smart Citations
“…8), 10) and 11). As pointed out above, obvious oscillations of normal spectral emissivity appears only at the first several min from the heating start in this work, whereas those reported in the literature 2,[8][9][10][11]14) appeared at very different heating times, typically from several seconds to an hour in the oxidizing surroundings.…”
Section: Strong Oscillation Of the Normal Spectral Emissivitysupporting
confidence: 49%
“…Campo et al 10) observed a number of weak oscillations over the wavelengths ranging from 1.28 to 25 μm at seven different heating times. Wen 11,14) observed few oscillations during the first-hour heating time. Pujana et al…”
Section: Strong Oscillation Of the Normal Spectral Emissivitymentioning
confidence: 98%
See 3 more Smart Citations